2005
DOI: 10.1111/j.1754-8845.2005.tb00624.x
|View full text |Cite
|
Sign up to set email alerts
|

Creativity in education

Abstract: Currently considerable interest is being shown in creativity by the government and bodies such as QCA and Ofsted. A ‘creativity agenda’ has emerged with important implications for teaching and learning in schools. Drawing on research literature, as well as work completed by Secondary PGCE English and Drama trainees, this paper aims to provoke discussion about how creativity in education is defined and the impact of more explicit understandings of creativity in classrooms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…Teaching experience might contribute to the richer conception to some extent (Al-Nouh et al, 2014). Nonetheless, the narrow and limited understanding of creativity in the research points out to the need to stress creativity in teacher education and training (Hodges, 2005;Vass, 2007;Howell, 2008;Anderson-Patton, 2009;Newton, L. & Beverton, 2012). Teachers need to realise that 'creativity is not mysterious, elitist or inaccessible' (Simmons & Thompson, 2008, p.606), and they can adopt elements of creativity when acting as a facilitator in their teaching (Fisher, 2005;Cremin & Barnes, 2014).…”
Section: Discussionmentioning
confidence: 96%
“…Teaching experience might contribute to the richer conception to some extent (Al-Nouh et al, 2014). Nonetheless, the narrow and limited understanding of creativity in the research points out to the need to stress creativity in teacher education and training (Hodges, 2005;Vass, 2007;Howell, 2008;Anderson-Patton, 2009;Newton, L. & Beverton, 2012). Teachers need to realise that 'creativity is not mysterious, elitist or inaccessible' (Simmons & Thompson, 2008, p.606), and they can adopt elements of creativity when acting as a facilitator in their teaching (Fisher, 2005;Cremin & Barnes, 2014).…”
Section: Discussionmentioning
confidence: 96%
“…Some researchers even included ethical (Cropley, 2001) and autonomical (Hodges, 2005;Sawyer, 2004) issues in creativity. Also, conceptions of creativity reflect cultural values, which may affect a person's experience of creativity and his or her ability to manifest it (Craft, 2003;Csikszentmihalyi, 1996;Sawyer, 2004;Sternberg, 2007).…”
Section: Foundations and Creativity In Mathematicsmentioning
confidence: 99%
“…If some students have had experiences with the tasks and others have not, those who have had these experiences will have an unfair advantage. We have also found that students are not as motivated to participate in a task if they have done exactly the same task before. The performance-based assessment could be combined with existing assessments to identify students for special life science programs for exceptionally talented students because it is fair to students from American Indian and Hispanic groups, and may be a fair assessment of other groups of students of color. The life science assessment can be used alone or in combination with other assessments to assess the quality of teaching in life science classrooms. The life science assessment can be used in classrooms to help teachers design and differentiate their lessons to meet students’ academic needs (Hodges, 2005; Pease et al, 2020; Sandri, 2013; Tracy, 2015). Teachers can use these tasks to determine the strengths of their students and then design instruction to meet these needs. If students have difficulty with open-ended problem solving but can solve closed and semiopen problems easily, then the teacher can start with these problems and gradually introduce more open-ended problems to give students opportunities to think about problems in creative ways, create new methods for solving them, and generate unusual solutions (Maker & Schiever, 2010).…”
Section: Suggested Usesmentioning
confidence: 99%